Host association and selection on salivary protein genes in bed bugs and related blood-feeding ectoparasites - Talbot, Benoit; Balvín, Ondřej; Vonhof, Maarten J; Broders, Hugh G; Fenton, Brock; Keyghobadi, Nusha (Royal Society open science, 2017)
Reciprocal selective pressures can drive coevolutionary changes in parasites and hosts, and result in parasites that are highly specialized to their hosts. Selection and host co-adaptation are better understood in endoparasites than in ectoparasites, whose life cycles may be more loosely linked to that of their hosts. Blood-feeding ectoparasites use salivary proteins to prevent haemostasis in the host, and maximize energy intake. Here we looked for signals of selection in salivary protein genes of ectoparasite species from a single genus (Cimex) that associate with a range of hosts including mammals (bats and humans) and birds (swallows). We analysed two genes that code for salivary proteins that inhibit platelet aggregation and vasoconstriction and may directly affect the efficiency of blood feeding in these species. Significant positive selection was detected at five codons in one gene in all bat-associated species groups. Our results suggest association with bats, versus humans or swallows, has posed a selective pressure on the salivary apyrase gene in species of Cimex.
Keywords: coagulation; apyrase; candidate genes; phylogenetics; nitrophorin